1995
DOI: 10.1073/pnas.92.7.2859
|View full text |Cite
|
Sign up to set email alerts
|

gp130 and c-Kit signalings synergize for ex vivo expansion of human primitive hemopoietic progenitor cells.

Abstract: ABSTRACTgpl3O, a signal-transducing receptor component of interleukin 6 (IL-6), associates with an IL-6 and IL-6 receptor (IL-6R) complex and transduces signals. To examine the role of gpl3O signaling in the expansion of human hemopoietic progenitor cells, we tested the effects of a recombinant soluble human and/or combination with other cytokines on purified human umbilical cord blood CD34+ cells, using methylcellulose clonal assay and suspension culture in the presence or absence of serum. A combination of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
83
3

Year Published

1997
1997
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(98 citation statements)
references
References 25 publications
12
83
3
Order By: Relevance
“…Supplementing in vitro primary hematopoietic cell cultures with either SF or Tpo, particularly in combination with other early-acting factors, can induce HSC division and increase the recovery of totipotent cells by preventing differentiation and/or facilitating self-renewal. 25,28,44,45 Consistent with these in vitro studies, primitive cell deficiencies have been described in mice with loss-of-function alleles in Tpo or SF pathways. Tpo Ϫ/Ϫ or c-Mpl Ϫ/Ϫ mice have reduced numbers of progenitor cells of multiple lineages, including CFU-Mk, CFU-GM, CFU-E, and CFU-granulocyte-erythrocyte-megakaryocytemacrophage (CFU-GEMM).…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Supplementing in vitro primary hematopoietic cell cultures with either SF or Tpo, particularly in combination with other early-acting factors, can induce HSC division and increase the recovery of totipotent cells by preventing differentiation and/or facilitating self-renewal. 25,28,44,45 Consistent with these in vitro studies, primitive cell deficiencies have been described in mice with loss-of-function alleles in Tpo or SF pathways. Tpo Ϫ/Ϫ or c-Mpl Ϫ/Ϫ mice have reduced numbers of progenitor cells of multiple lineages, including CFU-Mk, CFU-GM, CFU-E, and CFU-granulocyte-erythrocyte-megakaryocytemacrophage (CFU-GEMM).…”
Section: Discussionsupporting
confidence: 63%
“…While some single growth factors can maintain long-term repopulating cells in culture, multiple factors are required for expansion. 25,44,45 Recent findings indicate that both Tpo signaling (via JAK2) and SF signaling are required for in vitro self-renewal of multipotent hematopoietic cells. 46 However, expansion of long-term repopulating cells can be achieved in H2K-BCL-2 transgenic bone marrow cells with a single growth factor (SF), indicating that one of the in vitro requirements is inhibition of HSC apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…28 In addition, gp130 is ubiquitously expressed on CB-derived CD34 + cells. 34 As described above, most human CB-derived CD34 + cells did not express the IL- tively than IL-6 alone. In fact, Sui et al 35 have reported that a combination of sIL-6R and IL-6 dramatically stimulated the obtained in our series of experiments.…”
Section: Cytokinesmentioning
confidence: 82%
“…Mononuclear cells (MNCs) were separated by Ficoll density gradient centrifugation after depletion of phagocytes with silica (IBL) as described elsewhere (Imai et al, 1991). CB CD34+ cells were isolated from MNCs by using Dynabeads M-450 conjugated with CD34 monoclonal Ab (mAb) and DETACHaBEAD CD34 (Dynal) as described previously (Sui et al, 1995). CB CD34+107, CD34+10+ cells were puri®ed from CB CD34+ cells by cell sorting on FACS Vantage (Becton Dickinson).…”
Section: Primary Hematopoietic Cell Culturementioning
confidence: 99%